Life-history traits of the Magellan plunderfish Harpagifer bispinis (Forster, 1801) in the Beagle Channel (Tierra del Fuego, South America) - Llompart, Facundo Manuel; Fernandez, Daniel Alfredo; Aureliano, Daniel; la Mesa, Mario (Polar Biology)
The Magellan plunderfish Harpagifer bispinis is a small and benthic sub-Antarctic notothenioid commonly found in shallow waters of the Beagle Channel, whose biology is poorly known. Based on a seasonal sampling conducted throughout a year, we provide original data on some biological parameters, such as reproductive traits and age structure. The sampled population of Magellan plunderfish was sex balanced, showing no dimorphism in fish size and isometric body growth. Macroscopic and histological analyses of gonads enabled us to infer that this species is a total spawner, with a single annual spawning season during the austral winter. Total fecundity was considerably low (mean of 574 eggs per female), even compared with other harpagiferids. Based on daily increment counts made in juveniles, larval hatching took place between late September and early October, likely enhancing their survival during the warmer months. The Von Bertalanffy growth parameters, estimated from the length-at-age data pairs for the whole population, were L∞ = 80.7 (± 0.82), K = 0.25 (± 0.01), and t0 = − 2.31. The estimated growth performance (3.21) and life span (7 years) of H. bispinis were both comparable to those reported for their most closely related species, H. antarcticus. The life-history traits of Magellan plunderfish are discussed from an ecological and evolutionary perspective, through a comparative approach with their Antarctic counterparts. Fil: Llompart, Facundo Manuel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego, Antártida e Islas del Atlántico Sur. Instituto de Ciencias Polares, Ambientales y Recursos Naturales; Argentina Fil: Fernandez, Daniel Alfredo. Universidad Nacional de Tierra del Fuego, Antártida e Islas del Atlántico Sur. Instituto de Ciencias Polares, Ambientales y Recursos Naturales; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; ...